Rijksmuseum Research Library : Rijksmuseum - Rijksmuseum (2009)
[Dt.:] Die Forschungsbibliothek des Amsterdamer Rijksmuseums ist die größte kunsthistorische Bibliothek in den Niederlanden. Ihr Bestand umfasst Bücher, Reihen und Zeitschriften mit Bezug zur Sammlung des Museums, Auktions-, Ausstellungs- und Sammlungskataloge vom Mittelalter bis zum Beginn des 20. Jahrhunderts. Die Website der Bibliothek bietet Zugang zum Online-Katalog der Bibliothek und eine Suchfunktion innerhalb der ganzen Sammlung des Museums. - [Engl.:] The research library of the Rijksmuseum in Amsterdam is the biggest art history library in the Netherlands. The collection covers books, periodicals and journals relating to the museum's collection, auction and exhibition catalogues, trade and collection catalogues from the middle age to the dawn of the 20th century. The library's website provides access to the online library catalogue and has a search function for the entire collection of the museum.